Effect of using germinated for common vetch seeds Vicia sativa on growth performance of common carp Cyprinus carpio L. - Mohammad, Mahmoud A. (The Iraqi Journal of Veterinary Medicine, 2017)
This investigation was carried out to utilize common vetch Vicia sativa in formulating diets for 84 common carp Cyprinus carpio L. with initial weight 28±2g/fish were distributed randomly over seven experimental diets with three replications for each. The fish fed experimental diets for 56 days contained 30% and 45% of common vetch Vicia sativa of total diets which treated with germinated for 5 days (diet 2 and 3), 7 days (diet 4 and 5) and the last diets contained crude vetch (diet 6 and 7). The statistical analysis of data showed that the fish fed at diet 3 was significantly different (P≤0.05) compared to fish fed at another diets in total weight, total weight gain, relative growth rate, specific growth rate and feed conversion ratio. It is in conclusion germinated common vetch seed can be successfully used as an inexpensive plant protein source at level of 45% (germinated seed for 5 days) in common carp diets without adverse effect on fish performance.